Assessing the role of emotional mediation in explaining crossmodal correspondences involving musical stimuli - Spence, C (Brill Academic Publishers, 2019)
A wide variety of crossmodal correspondences, defined as the often surprising connections that people appear to experience between simple features, attributes, or dimensions of experience, either physically present or else merely imagined, in different sensory modalities, have been demonstrated in recent years. However, a number of crossmodal correspondences have also been documented between more complex (i.e., multi-component) stimuli, such as, for example, pieces of music and paintings. In this review, the extensive evidence supporting the emotional mediation account of the crossmodal correspondences between musical stimuli (mostly pre-recorded short classical music excerpts) and visual stimuli, including colour patches through to, on occasion, paintings, is critically evaluated. According to the emotional mediation account, it is the emotional associations that people have with stimuli that constitutes one of the fundamental bases on which crossmodal associations are established. Taken together, the literature that has been published to date supports emotional mediation as one of the key factors underlying the crossmodal correspondences involving emotionally-valenced stimuli, both simple and complex.